Proceedings of the 8th ACM International Workshop on Multimedia Information Retrieval 2006
DOI: 10.1145/1178677.1178705
|View full text |Cite
|
Sign up to set email alerts
|

Joint categorization of queries and clips for web-based video search

Abstract: Building a video search engine on the Web is a very challenging problem. Compared with web page search, video search has its unique characteristics (such as high volume of data for each video, existence of multi-modal information including meta-data, visual content, audio, closed caption, etc). In this paper, we investigate some promising approaches to boosting the search relevance of a large scale video search engine on the Web. The contribution of our work is three-fold. (1) We developed a specialized video … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Zhang et al [20] classify videos with respect to five categories (movies, music, fun, finance and news) by using binary classifiers trained on two separated feature sets -meta-data (i.e., text) and content (i.e., visual). Their experiments demonstrated that category accuracy depends on the type of the classifier and therefore they take advantage of this prior knowledge by using a voting based category-dependent scheme.…”
Section: Video and Image Classificationmentioning
confidence: 99%
“…Zhang et al [20] classify videos with respect to five categories (movies, music, fun, finance and news) by using binary classifiers trained on two separated feature sets -meta-data (i.e., text) and content (i.e., visual). Their experiments demonstrated that category accuracy depends on the type of the classifier and therefore they take advantage of this prior knowledge by using a voting based category-dependent scheme.…”
Section: Video and Image Classificationmentioning
confidence: 99%
“…The diverse and complex nature of Web videos enforced researchers to employ different combinations of modalities, such as audio, visual, and textual, for automatic Web video classification. Metadata and content‐based binary classifiers were designed to classify videos into five categories (music, movies, fun, news, and finance). Their experiments showed that the category accuracy relies on the type of the classifier, and hence they took advantage of this preceding knowledge by employing a voting‐based category‐dependent scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Query-Classes for Web Video Collections: Zhang et al [6] describe an application of query-class-dependency for video search in a domain entirely different from TRECVID: large-scale web-based video clip search. Web video clips are almost entirely different in content than the broadcast news clips in the TRECVID datasets, and the types of users (typical consumers for the web and news analysts or producers for TRECVID) are also quite different.…”
Section: B Multimodal Search Over Image and Video Collectionsmentioning
confidence: 99%